FENOMENA FEAR OF MISSING OUT (FOMO) DALAM GAYA HIDUP THRIFTING BERMEREK PADA MAHASISWA UNIVERSITAS SULTAN AGENG TIRTAYASA DI ERA MEDIA SOSIAL - Serly Putri Hidayat; Stevany Afrizal (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
This study examines the phenomenon of Fear of Missing Out (FOMO) within branded thrifting practices among students at Sultan Ageng Tirtayasa University. Thrifting, which was initially driven by the need to find affordable secondhand clothing, has now developed into a consumption pattern strongly shaped by social media. This research aims to explore students’ experiences, motivations, and the meanings they construct when engaging in branded thrifting using a qualitative phenomenological approach. Data were collected through in-depth interviews, observations of social media content, and documentation related to thrifting activities. Pierre Bourdieu’s theory of social practice is used to understand how habitus, capital, and field influence these practices. The findings show that social media plays a significant role in encouraging students’ interest in branded thrifting through review content, fashion hauls, shop recommendations, and live shopping sessions. Continuous exposure to these trends creates a sense of urgency for some students to keep up with certain styles so as not to feel left behind by their peers. This condition fosters FOMO, which later shapes students’ decisions when selecting and purchasing branded thrift items. Ultimately, branded thrifting becomes not only an economical choice but also a medium for self-expression, identity formation, and maintaining social presence both on campus and in digital spaces.